Prevalence of Dental Caries and Fissure Sealant in the First Permanent Molars among Patients Attending College of Dentistry, Erbil, Iraq. (A Retrospective Study) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2024)
Background: The FPM is especially helpless against dental caries due to its unmistakable shape, early emission, and area in the mouth, unveiling it a significant wellbeing concern around the world. The objectives of this examination project at Erbil's School of Dentistry, Hawler Clinical College, are to decide the way that normal dental caries is in first long-lasting molars of pediatric patients, how normal gap sealants are, and to make a norm for caries preventive estimates all through the country.Materials and Methods:The information for the review examination came from 263 pediatric patients (129 young men and 134 young ladies) with ages going from 5 to 16 and were assembled somewhere in the range of 2021 and 2022. We observed segment subtleties including orientation, age, and FPM status. Caries in the teeth were analyzed on the surfaces of the occlusal teeth utilizing the DMFT\S file. We involved SPSS Version:28 for our factual exploration, and the chi-square test showed that FPM caries differed essentially with age.Results:Findings showed that tooth caries was more common than fissure sealants, and that females had a greater incidence of occurrence than boys. The percentage of caries was 60.5% greatest in the age range of 5-8. Conclusion:The findings of this research emphasise the need of developing age-appropriate treatments and tailored preventative measures that take gender into account.